Peritoneal hydatid cyst - Otoya, Enrique (2019)
A 29 year old male patient with abdominal pain of two months, presence of mass at the level of lower hemiabdomen, a CT scan that showed a septated cystic tumor in the peritoneum and positive Western blot for hydatid disease. It was confirmed the diagnosis of peritoneal hydatid cyst, carrying out medical and surgical management.